Iodine adequacy in reproductive age and pregnant women living in the Western region of Saudi Arabia - Firas Azzeh; Bassem Refaat (BMC, 2020)
Abstract Background Despite the serious maternal and foetal complications associated with iodine deficiency during pregnancy, surveys related to pregnant women in the Kingdom of Saudi Arabia (KSA) are lacking. This study, therefore, measured urine iodine concentrations (UIC) alongside the potential socioeconomic factors contributing towards iodine inadequacy in reproductive age and pregnant Saudi women from the Western province of KSA. Methods Spot urine samples were collected from 1222 pregnant and 400 age-matched non-pregnant/non-lactating reproductive age women. The socioeconomic characteristics were obtained through a structured questionnaire. The WHO criteria for iodine sufficiency in non-pregnant (100-199 μg/L) and pregnant (150-249 μg/L) women were applied. Results The median UIC in the non-pregnant women (101.64 μg/L; IQR: 69.83-143.55) was at the lowermost WHO recommended cut-off, whereas the pregnant group was iodine deficient (112.99 μg/L; IQR: 81.01-185.57). Moreover, the median UIC was below adequacy across the different trimesters. The use of non-iodised salt significantly increased the risk of iodine deficiency in the non-pregnant (OR = 2.052; 95%CI: 1.118-3.766) and pregnant women (OR = 3.813; 95%CI: 1.992-7.297), whereas taking iodine supplements significantly lowered the risk in both groups (OR = 0.364; 95%CI: 0.172-0.771 and OR = 0.002; 95%CI: 0.001-0.005, respectively). Passive smoking was also an independent risk factor for iodine deficiency in the non-pregnant (OR = 1.818; 95%CI: 1.097-3.014) and pregnant (OR = 1.653; 95%CI: 1.043-2.618) groups. Additionally, BMI correlated independently and significantly with median UIC in the non-pregnant and pregnant populations. However, multiparity (OR = 3.091; 95%CI: 1.707-5.598) and earning below the minimum wage (2.520; 95%CI: 1.038-6.119) significantly increased the risk of iodine deficiency only in the non-pregnant women. Conclusions This study is the first to show borderline iodine sufficiency in reproductive age Saudi women from the Western province, whereas mild iodine deficiency was observed in the pregnant population and could represent a serious public health problem. This study also advocates the necessity to establish routine iodine dietary advice services by the health authorities to foster adequate iodine intake in pregnant women to avoid the perilous consequences of iodine deficiency on maternal-foetal health.